Reallocation of Resources within the National Productive System in Bolivia A View from the Perspective of Tradable and Non-Tradable Goods - Sergio G. Villarroel Böhrt (Centro de Investigación y Docencia Económicas, A.C., 2007)
This paper explores Bolivia's current unemployment situation taking into account the reallocation of resources within the aggregate supply. The origin of this internal imbalance is due to negative impacts of external real exchange rate (RER) shocks, as well as to changes in the destination of foreign direct investment (FDI) among different sectors of the economy. The model used to explain the imbalance is based on the Dependent Economy theoretical framework, in which production in a small open economy is disaggregated into tradable and non-tradable goods. Under this production scheme, any RER movement in terms of appreciation or depreciation produces a displacement of resources, either along the production possibilities frontier or through the unemployment zone. After demonstrating that the RER suffered an important appreciation in 1997, a model of the aggregate-supply function is constructed considering two variable outputs (tradable and non-tradable goods) and two variable inputs (capital and labor), suggesting in the end the existence of a slow restructuring process at the expense of unemployment of the labor force.